Pemilihan Lokasi Kantor Menggunakan Metode Analytical Hierarchy Process (AHP) (Studi Kasus: PT. Monang Sianipar Abadi Surakarta) - Aditha Capryani; Alviandi Wahyu Nugroho; Virda Hersy Lutviana Saputri; Yuniaristanto - (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2016)
PT. Monang Sianipar Abadi (MSA Kargo) Surakarta had experienced problems such as delays in delivery of goods. One cause of the delay problem is there are two places for the delivery of goods, which is headquarters in Pawulan, Colomadu and warehouse located near Airport Adisumarmo. In connection with these problems, improvements are expected to tackle the problem of delay delivery of goods caused by places for the delivery of goods. Repairs carried out by determining the best location to be the location of office shipping the items. Determination of the place of delivery of goods using fast and accurate method is the method of Analytical Hierarchy Process (AHP). The process of determining the place of delivery of goods based on four criteria, namely within the main warehouse (warehouse near the plane at the airport Adisumarmo), ease of access by customers, building area, and the availability of facilities. Based on the results obtained total global priority, then the decision can be taken the nicest locations in determining the location of the office is the location S2 is in Pawulan, Colomadu because it has the highest total global priorities, namely 0.638. However, the site has the disadvantage that the distance is far enough away from the main warehouse so it can be added to a solution is by adding a fleet of delivery.